Rapid and parallel changes in activity and mRNA of intestinal peptidase to match altered dietary protein levels in juvenile house sparrows (Passer domesticus) - Brun, Antonio (2021)
Although dietary flexibility in digestive enzyme activity (i.e. reaction rate) is widespread in vertebrates, mechanisms are poorly understood. When laboratory rats are switched to a higher protein diet, the activities of apical intestinal peptidases increase within 15 h, in some cases by rapid increase in enzyme transcription followed by rapid translation and translocation to the intestine's apical, brushborder membrane (BBM). Focusing on aminopeptidase-N (APN), we studied intestinal digestive enzyme flexibility in birds, relying on activity and mRNA data from the same animals. Our model was nestling house sparrows (Passer domesticus), already known to modulate intestinal peptidase activity when switching between lower and higher protein diets. Twenty-four hours after a switch from an adequate, lower protein diet to a higher protein diet, APN activity was increased in both whole intestinal tissue homogenates and in isolated BBM, but not at 12 h post-diet switch. Twenty-four hours after a reverse switch back to the lower protein diet, APN activity was decreased, but not at 12 h post-diet switch. Changes in APN activity in both diet switch experiments were associated with parallel changes in APN mRNA. Although transcriptional changes seem to be an important mechanism underlying dietary modulation of intestinal peptidase in both nestling house sparrows and laboratory rodents, the time course for modulation in nestlings seemed slower (taking approximately twice as long) compared with laboratory rodents. It may be ecologically advantageous if nestlings biochemically restructure their gut in response to a sustained increase in insects and protein intake rather than one or a few lucky insect meals.